Dynamic interplay of alkali cations and a natural organic binder in the microstructural evolution of Cu2ZnSnS4 thin films prepared from Cu2ZnSnS4 powder-containing inks. Issue 49 (11th September 2019) - Mutiari, Anies; Bansal, Neha; Hamid, Raad; Artner, Martin; Mayer, Veronika; Roth, Juergen; Weil, Matthias; Wibowo, Rachmat Adhi
Abstract : The use of pre-synthesised Cu2 ZnSnS4 (CZTS) sub-micron powders as a raw material for preparing CZTS thin films for photovoltaic absorber applications is examined. Abstract : The use of pre-synthesised Cu2 ZnSnS4 (CZTS) sub-micron powders as a raw material for preparing CZTS thin films for photovoltaic absorber applications is examined. A challenge in preparing photovoltaic device-relevant CZTS films from submicron powders is producing a dense CZTS film by a sintering process. This is due to the nature of non-unimodal particle size and morphology that typically lead to the formation of pores after sintering. This work aimed to study the sintering behaviour of CZTS films that were prepared from a CZTS powder-containing ink. Complementary DT-TGA and in situ X-ray powder diffraction studies at elevated temperature reveal that the tetragonal kesterite phase in the as-sintered CZTS film is stable until 620 °C. An effective tendency of CZTS powder towards film recrystallisation occurs when alkali cations (Na and/or K) are added to the ink. For the first time, effects of additional natural gum as a binder in the CZTS powder-containing ink on the CZTS film sintering behaviour were also investigated. Contrary to the positive effects of alkali addition, the binder inhibits recrystallisation of CZTS. Therefore, the amount of binder was controlled in a quantity large enough to modify the ink viscosity, but low enough to allow large CZTS grain growth during sintering. A dense and compact as-sintered CZTS film can be produced from a CZTS powder-containing ink with 10 mol% Na and 2 mol% K alkali addition along with 3 wt% binder addition.